Political Narrations Antigone, the Melian Dialogue, Michael Kohlhaas, the Grand Inquisitor and Ragtime - Juchler, Ingo (Springer International Publishing, 2018)
This book analyzes narrations embedded in political disputes, allowing readers to gain a deeper understanding of modern political reality. The author explores this theme in readings of the Sophocles tragedy Antigone, the Melian Dialogue of Thucydides, Heinrich von Kleist's novella Michael Kohlhaas, Fyodor Dostoevsky's The Grand Inquisitor and E.L. Doctorow's Ragtime novel, taking into account the relevant interdisciplinary aspects of the narratives. His study of these four narrations focuses on key political concepts, such as might and right, self-interest, legality and justice, the nation-state and democracy, and relates them compellingly to current actuality. Since narrations can exert comprehensive and lasting influence on individuals' political discernment, this systematic analysis allows for a better comprehension of politics in education and civics.